Representation of commutants for composition operators induced by a hyperbolic linear fractional automorphisms of the unit disk - Linchuk, Yu. S. (Methods of Functional Analysis and Topology, 2008)
We describe the commutant of the composition operator induced by a hyperbolic linear fractional transformation of the unit disk onto itself in the class of linear continuous operators which act on the space of analytic functions. Two general classes of linear continuous operators which commute with such composition operators are constructed.